Synthesis and structure–activity relationship of dehydrodieugenol B neolignans against Trypanosoma cruzi - Sear, CE; Pieper, P; Amaral, M; Romanelli, MM; Costa-Silva, TA; Haugland, MM; Tate, JA; Lago, JHG; Tempone, AG; Anderson, EA (American Chemical Society, 2020)
Trypanosoma cruzi is the etiologic agent of Chagas disease, which affects over seven million people, especially in developing countries. Undesirable side effects are frequently associated with current therapies, which are typically ineffective in the treatment of all stages of the disease. Here, we report the first synthesis of the neolignan dehydrodieugenol B, a natural product recently shown to exhibit activity against T. cruzi. Using this strategy, a series of synthetic analogues were prepared to explore structure–activity relationships. The in vitro antiparasitic activities of these analogues revealed a wide tolerance of modifications and substituent deletions, with maintained or improved bioactivities against the amastigote forms of the parasite (50% inhibitory concentration (IC50) of 4–63 μM) and no mammalian toxicity (50% cytotoxic concentration (CC50) of >200 μM). Five of these analogues meet the Drugs for Neglected Disease Initiative (DNDi) “hit criteria” for Chagas disease. This work has enabled the identification of key structural features of the natural product and sites where scaffold modification is tolerated.